Solid encapsulation of lauric acid into “empty” V-type starch: structural characteristics and emulsifying properties - Huang, Liang; Li, Songnan; Tan, Chin Ping; Feng, Yinong; Zhang, Bin; Fu, Xiong; Huang, Qiang (Elsevier, 2021)
Lauric acid was introduced into “Empty” V-type starch using a solid encapsulation method. The structural characteristics and emulsifying properties of the starch-fatty acid complex (SFAC) were explored as a function of the complexing temperature. X-ray diffraction and differential scanning calorimetry confirmed that SFAC was mainly composed of type-I amylose inclusion complexes. Contact angle measurements revealed that the hydrophobic properties of SFAC were closely related to the temperature-regulated complex index. The particle size range of SFAC gradually increased as the complexing temperature increased. The SFAC-stabilized Pickering emulsion at c of 5% and Φ of 40–60% possessed a small droplet size and long-term storage stability for up to 30 days, resulting from the formation of a gel-like network. This study provides new insight into the design of hydrophobic modified starch as a novel and multifunctional emulsifier and is of great help in the development of starch-based Pickering emulsion gels.